Peningkatan Efektivitas Administrasi Publik melalui Pendampingan Penyusunan Dokumen Perencanaan Pembangunan Daerah di Bapperida Kabupaten Bangkalan - Sistifanie Putri Handayani; Auliya Zulfatillah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The mentoring activity for preparing regional development planning documents at Bapperida Bangkalan Regency is part of a community service program aimed at improving the effectiveness of public administration. During the program, students were directly involved in collecting and processing data, analyzing program performance indicators, and assisting in drafting and evaluating planning documents such as the RKPD, RPJMD, and RPD. This activity also supported the budgeting process, program consistency assessment, and public service performance measurement through the Community Satisfaction Survey (SKM). The results of the mentoring program show that collaboration between academia and local government can improve work efficiency, the quality of planning documents, and the capacity of civil servants in developing data-driven policies. This activity not only benefited the institution but also served as a real-world learning experience for students in understanding public administration practices at the regional level.